2015
DOI: 10.1109/led.2015.2451005
|View full text |Cite
|
Sign up to set email alerts
|

Highly Robust Flexible Oxide Thin-Film Transistors by Bulk Accumulation

Abstract: We report the achievement of flexible oxide thin-film transistors (TFTs) that are highly robust under mechanical bending stress. Fabricated on solution-processed polyimide (PI), the oxide TFTs employ the dual-gate structure with an amorphous-indium-gallium-zinc oxide (a-IGZO) semiconductor, silicon-dioxide gate-insulators, and molybdenum gate and source/drain electrodes. High mechanical stability is achieved by shorting the two gates together to induce bulk-accumulationa condition in which the channel accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…It is impressive that the Δ V TH values were estimated to be as small as +1.2 and −2.1 V after a lapse of 10 4 s during the PBS and NBS tests, respectively, even at an R c of 1 mm. These obtained results evidently suggested that our proposed flexible VTFTs showed superior bending stability comparable to the previously reported devices with various different structures. Furthermore, the excellent operation stabilities at mechanically bending situations hardly been reported for the TFTs with vertical-channel structures. Consequently, the proposed flexible VTFTs achieved excellent device performance by effectively solving technical issues such as appropriate choice of materials and optimized designs of process conditions.…”
Section: Results and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is impressive that the Δ V TH values were estimated to be as small as +1.2 and −2.1 V after a lapse of 10 4 s during the PBS and NBS tests, respectively, even at an R c of 1 mm. These obtained results evidently suggested that our proposed flexible VTFTs showed superior bending stability comparable to the previously reported devices with various different structures. Furthermore, the excellent operation stabilities at mechanically bending situations hardly been reported for the TFTs with vertical-channel structures. Consequently, the proposed flexible VTFTs achieved excellent device performance by effectively solving technical issues such as appropriate choice of materials and optimized designs of process conditions.…”
Section: Results and Discussionsupporting
confidence: 82%
“…Recently, the explosive demand for flexible electronics has led to the development of mechanically flexible, rollable, or stretchable forms of electronics devices and systems. One of the promising approaches to realize these various flexible applications is to change the structures of key devices including thin-film transistors (TFTs). Conventionally, the devices fabricated with planar structures, in which functional layers are subject to be mechanically stained, experienced degradation in device performance due to the development of microcracks into the device plane . Alternatively, the vertical-channel structure thin-film transistors (VTFTs) exhibit high resistance to mechanical bending stress because they can be completely free from in-plane cracking of the active channel layer.…”
Section: Introductionmentioning
confidence: 99%
“…The best results for TFT performance was obtained at 200 nm. The GI thickness asymmetry (here in this case 50 nm) is not surprising and multiple reports having asymmetric GI thickness of the DG structured BCE TFTs [17], [21], [22], [27], [29], and coplanar TFTs [30] are reported.…”
Section: Experiments a Coplanar Tft Fabricationmentioning
confidence: 65%
“…No depletion for the former type whereas clear depletion property for the latter type. Comparing with SG TFT, improved transfer and higher output is a well-established phenomenon for the DG TFT [17]- [22], [26], [27]. The threshold voltage (V th ), maximum field-effect mobility (µ fe−Max ), and subthreshold swing (SS) for DG and SG TFT by measurement is 0.1 V, −1.8 V, 18.4 cm 2 /V.s, 13.52 cm 2 /V.s, 0.35 V/dec., and 0.85 V/dec.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation